Are all schools created equal? Learning environments in small and large public high schools in New York City. (June 2016) - Schwartz, Amy Ellen; Stiefel, Leanna; Wiswall, Matthew
Highlights: We use a unique dataset to examine students' attitudes about school learning environment. We find that students attending a new small school perceive their environments similarly to those attending a large school. In general, small size does not necessarily generate superior learning environments. Abstract: Over the past two decades, high school reform has been characterized by a belief that "smaller is better." Much of the expected academic benefit from attending small schools has been credited to their better learning environments. There is little empirical support for this claim, however, and the existing research fails to provide causal evidence. Moreover, recent studies in New York City have shown that students attending newly created small schools do better academically relative to students attending both large and older established small schools. Are these differences in academic outcomes also mirrored by differences in learning environments? In this paper, we address this question by exploring the impact of attending large compared to small high schools on students' learning environments, considering the differences between small high schools formed in two different eras with different missions and resources. We use a unique data set of school and student-level data from New York City public high school students entering 9th grade in 2008–09 and 2009–10 to examine students' attitudes about school learning environments along three dimensions: interpersonal relationships, academic expectations and support, and social behavior and safety. While OLS results show that students attending small schools (new and old) perceive better learning environments, instrumenting for selection into these schools challenges those results. In general, it is not clear that small schools provide better learning environments than large schools. Our results challenge the conventional wisdom that the higher academic performance of students in small schools is driven by a better learning environment.